Complexities of Racial Identity Development for Asian Pacific Islander Desi American (APIDA) College Students. Issue 160 (20th December 2017) - Chan, Jason
Abstract: Higher education research increasingly acknowledges the multiple identities and communities within the Asian Pacific Islander Desi American (APIDA) student population. This chapter explores the complex and multifaceted aspects of APIDA students and offers key considerations for student affairs practitioners working with today's APIDA student population.